Flora and Fauna Lexicon in Village Naming in North Aceh - Istiqamah Istiqamah; Chandri Febri Santi; K. J. Vargheese (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
The aim of this study is to uncover the flora and fauna lexicons in village nomenclature in North Aceh Regency that represents ecological knowledge and cultural values of an agrarian community. This study proceeds on the basis of the premise that toponymy is more than a two-dimensional code for administration but, rather, represents a language system where the mutual human-environmental relationship has been historically recorded. The study utilized a qualitative ethnolinguistic methodology supplemented by descriptive quantitative documentation and semi-structured interviews. For data analysis, the study used the Miles and Huberman interactive model, which consists of data condensation, data display, and conclusion drawing and verification. Results reveal that in the settlement’s names, flora components over dominate fauna ones by villagers reflecting agrarian interest and stable vegetation scenery. There are monomorphemic as well as polymorphemic forms and there is a prevalence of the [locational marker + natural lexicon] combination. Semantically, the flora and fauna lexis bear denotative meanings which refer to not only biological matters but also connotative meanings like fertility, protection, authority, trade as well as food security. This evidence suggests village naming in North Aceh is a patterned and functional linguistic system that functions as an ecological archive of the past, and as an index of group identity. The flora and fauna lexicons in the North Aceh village names mentioned above, can thus be seen as a document on ecology and culture important to conserve local knowledge.   Tujuan Penelitian ini adalah mengungkap leksikon flora dan fauna dalam penamaan desa di Kabupaten Aceh Utara sebagai cermin pengetahuan ekologis dan nilai budaya masyarakat agraris. Asumsi yang mendasari kajian ini bahwa toponimi bukan semata label administratif tetapi merupakan sistem linguistik yang merekam relasi historis manusia dan lingkungan. Penelitian menggunakan pendekatan kualitatif-etnolinguistik dengan dukungan data kuantitatif deskriptif melalui dokumentasi dan wawancara semi-terstruktur. Analisis data dilakukan menggunakan model Miles dan Huberman yang meliputi kondensasi data, penyajian data, serta penarikan dan verifikasi kesimpulan. Hasil penelitian menemukan bahwa unsur flora mendominasi nama desa dibandingkan dengan unsur fauna, yang mencerminkan orientasi agraris dan stabilitas lanskap vegetatif. Sekaligus secara morfologis, ditemukan pola monomorfemis dan polimorfemis dengan struktur dominan [penanda lokasi + leksikon alam]. Secara semantik, leksik flora dan fauna tidak hanya memiliki makna denotatif sebagai entitas biologis namun juga memuat makna konotatif seperti kesuburan, perlindungan, otoritas, perdagangan, dan ketahanan pangan. Temuan ini mendukung bahwa penamaan desa di Aceh Utara merupakan sistem linguistik yang terstruktur dan fungsional sebagai arsip ekologis serta identitas kolektif masyarakat. Dengan demikian, leksion flora dan fauna desa di Aceh Utara dapat dipahami sebagai dokumentasi ekologis dan kultural yang relevan dalam konteks pelestarian pengetahuan.